Assessment of dietary exposure of young Chinese children to aluminium residues. Issue 4 (3rd April 2019) - Cao, Pei; Liu, Ai-Dong; Yang, Da-Jin; Liang, Jiang; Wang, Xiao-Dan; Xu, Hai-Bin; Ma, Ning
ABSTRACT: The aim of this study was to assess the Al dietary exposure of young Chinese children aged 0–3 years via formulae, complementary foods and wheat-based foods. Al residue data were obtained from the national food contamination monitoring programme from 2013 to 2016, encompassing 13, 833 samples of 12 food items with a detection rate of 76.0%. Food consumption data were gathered from the China National Food Consumption Survey conducted in 2015, comprising 20, 172 children aged 0–3 years old. The mean dietary exposure to Al for the general population of young Chinese children was estimated at 0.76 mg/kg bw/week, which does not exceed the PTWI. The 97.5th percentile intakes of Al reached 3.42 mg/kg bw/week, more than 1.7 times the PTWI. Wheat-based foods contributed 80.5% of the Al intake for the general population of young Chinese children, while formulae and complementary foods accounted for 19.5% of the total intake. The dietary intake of Al from formulae and complementary foods accounted for 6.0% and 1.6% of PTWI, respectively. These findings suggested that dietary exposure to Al among the general population of young Chinese children was lower than the PTWI and that there are no health concerns related to this level of Al intake. However, more attention should be placed on the health risks associated with Al exposure from wheat-based foods for young consumers with high food consumption in China (97.5th percentile)